Upaya Peningkatan Ekspor Sektor Usaha Mikro, Kecil dan Menengah Melalui Peningkatan Daya Saing Produk - . Rasbin; Ari Mulianta Ginting (Pusat Penelitian, Badan Keahlian DPR RI, 2011)
The ability of Micro, Small and Medium-sized Enterprises (UMKM) to survive amid globalization and world trade liberalization is highly important to Indonesia for at least two reasons. First, SMEs have historically been one of the key economic actors in the Indonesian economy, accounting for over 90 percent of all the enterprises across sectors and providing employment opportunities for over 90 per cent of the country’s total workforce. Second, the Indonesian trade regime has shifted significantly from a highly protected market to a more open economic system. By focusing on SMEs in Indonesia, this paper analyzes how to increase the purchasing power of demand from other country, and government’s efforts of infra-structure better of, product standardisation, and good governance to SMEs that are verry important to implement. It is also, the government, especially at the district level (e.g. provincial or municipal), have a best role to play, such as by providing technicalassistance, information, soft loans, as well as in facilitating the cooperation between SMEs and local universities, R&D institutes, and business associations.